Analisis Optimalisasi pada Usaha Mikro, Kecil dan Menengah (UMKM) Makanan Ringan di Kota Pontianak - Andry Lim (MABIS, 2022)
In running the UMKM business, business competition is not a new thing, both large-scale and small-scale businesses. The current high business growth creates very high competition. This situation requires entrepreneurs to use various strategies in their marketing process by carrying out an important entrepreneurial orientation in improving business performance that reflects the extent to which business actors can identify and exploit untapped opportunities. UMKM make a major contribution to the Indonesian economy, both in terms of the number of business units and employment. Companies are required to understand the right entrepreneurial orientation strategy, good market orientation and correct product innovation. The purpose of this study is to analyze and understand the effect of entrepreneurial orientation, market orientation and product innovation on marketing performance. The sample used was 100 respondents from a population of 406 snack food business actors in the city of Pontianak. The research method used is a causal study that aims to find a causal relationship between each variable with the data collection method using a questionnaire with quantitative analysis techniques using the SPSS version 22 model. The results show that the variables of entrepreneurial orientation, market orientation and product innovation have a significant effect on marketing performance.Keywords: UMKM Business Optimization